Crosstalk between thyroid CSCs and immune cells: basic principles and clinical implications - Li, Xiaoxiao; Han, Hengtong; Yang, Kaili; Li, Shouhua; Ma, Libin; Yang, Ze; Zhao, Yong-xun (Frontiers in Immunology, 2024)
Thyroid cancer has become the most common endocrine malignancy. Although the majority of differentiated thyroid cancers have a favorable prognosis, advanced thyroid cancers, iodine-refractory thyroid cancers, and highly malignant undifferentiated carcinomas still face a serious challenge of poor prognosis and even death. Cancer stem cells are recognized as one of the central drivers of tumor evolution, recurrence and treatment resistance. A fresh viewpoint on the oncological aspects of thyroid cancer, including proliferation, invasion, recurrence, metastasis, and therapeutic resistance, has been made possible by the recent thorough understanding of the defining and developing features as well as the plasticity of thyroid cancer stem cells (TCSCs). The above characteristics of TCSCs are complicated and regulated by cell-intrinsic mechanisms (including activation of key stem signaling pathways, somatic cell dedifferentiation, etc.) and cell-extrinsic mechanisms. The complex communication between TCSCs and the infiltrating immune cell populations in the tumor microenvironment (TME) is a paradigm for cell-extrinsic regulators. This review introduces the current advances in the studies of TCSCs, including the origin of TCSCs, the intrinsic signaling pathways regulating the stemness of TCSCs, and emerging biomarkers; We further highlight the underlying principles of bidirectional crosstalk between TCSCs and immune cell populations driving thyroid cancer progression, recurrence, or metastasis, including the specific mechanisms by which immune cells maintain the stemness and other properties of TCSCs and how TCSCs reshape the immune microenvironmental landscape to create an immune evasive and pro-tumorigenic ecological niche. Finally, we outline promising strategies and challenges for targeting key programs in the TCSCs-immune cell crosstalk process to treat thyroid cancer.